SISTEM INFORMASI LOKASI SEJARAH PAHLAWAN SULAWESI SELATAN MENGGUNAKAN ALGORITMA SEQUENTIAL SEARCH BERBASIS ANDROID - Pujianti Wahyuningsih; Nur Mustika (LPPM Poltek ST Paul, 2020)
Indonesia is a country that has heroes in every region, one of which is South Sulawesi. One of the obstacles for the younger generation today is the lack of knowledge and understanding of the history of regional heroes. The purpose of this study is to build a hero historical location information system with an android-based sequential search algorithm. The sequential search method is a search method in stages from beginning to end in reaching the desired point. The result of this research is to show historical information about heroes and information about South Sulawesi. This application also displays the location of historical places in South Sulawesi so that users of this application can find the right path to reach the desired point